Students' Perspectives and Experiences About the Elements of Quiziz Gamification in Mathematics Learning - Margaretha Madha Melissa; Leonardo Amaris Liaupati; Rado Maison Silalahi; Christina Ratna Wikaningtyas (Jurnal Mercumatika : Jurnal Penelitian Matematika dan Pendidikan Matematika, 2022)
The purpose of this study was to describe students' perspectives and experiences regarding Quizizz's features: leaderboards, points, power-ups, redemption questions, and answer keys in online mathematics learning during the covid-19 pandemic. The subjects of this study were 32 students of class X MIPA at a private high school in Yogyakarta. Subjects took twice quizzes, then filled out an open questionnaire about students' perspectives and experiences regarding the five Quizizz features. Data analysis was carried out using the network analysis method, but the construction of the themes was done manually. The results of the study are as follows. Leaderboards motivate subjects to play better. Points affect the subject's motivation. The number of points causes the subject to be provoked to rush to work on the problem. Power-ups are considered a subject of appreciation but can also be considered strange and disruptive to the game. Redemption Questions is a feature that the subject has been waiting for. Subjects remember the correct answers in preparation for the Redemption Questions. The answer key as feedback is used to study material and self-evaluation. All of these features except the leaderboards were deemed the subject unsuitable for application to quizzes in the context of an exam.